Student Behaviour Management: An Effect of Social Media on Building Character - Hasan Baharun; Rojab Muhammad Al-Idrisi Al-Hasani; Hilalah Tamami Nabila Sari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This paper aims to analyze social media's impact on student character formation in one of the junior high schools in Probolinggo Regency, East Java, from the perspective of social identity. This study used a qualitative approach with a case study, in which researchers used interviews, observation and documentation to obtain valid and authentic data. The data analysis technique is carried out circularly, from data reduction to data presentation and conclusion. The study results show three motivations behind the character changes in students from the perspective of social identity: self-enhancement and positive distinctiveness, uncertainty reduction, and optimal distinctiveness. These three things can positively and negatively impact the dynamics of changes in children's character. Therefore, teachers have a vital and strategic role in building children's character so they have character resilience amid the rapid flow of technology and information development.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//